2004
DOI: 10.1021/bi0484421
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of a Quercetin 2,3-Dioxygenase from Bacillus subtilis Suggests Modulation of Enzyme Activity by a Change in the Metal Ion at the Active Site(s)

Abstract: Common structural motifs, such as the cupin domains, are found in enzymes performing different biochemical functions while retaining a similar active site configuration and structural scaffold. The soil bacterium Bacillus subtilis has 20 cupin genes (0.5% of the total genome) with up to 14% of its genes in the form of doublets, thus making it an attractive system for studying the effects of gene duplication. There are four bicupins in B. subtilis encoded by the genes yvrK, yoaN, yxaG, and ywfC. The gene produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
178
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(192 citation statements)
references
References 27 publications
12
178
0
1
Order By: Relevance
“…designated strain FLA (flavonol utilization) was characterized with divalent Fe, Ni, and Co cofactors (43). The QDO from B. subtilis, has been characterized with divalent Fe, Mn, and Co cofactors (44) and tested for activity with divalent Mg, Ni, and Cd (45). It has been suggested that exchange of the active-site metal ion may allow biological modulation of enzyme activity (45).…”
Section: Resultsmentioning
confidence: 99%
“…designated strain FLA (flavonol utilization) was characterized with divalent Fe, Ni, and Co cofactors (43). The QDO from B. subtilis, has been characterized with divalent Fe, Mn, and Co cofactors (44) and tested for activity with divalent Mg, Ni, and Cd (45). It has been suggested that exchange of the active-site metal ion may allow biological modulation of enzyme activity (45).…”
Section: Resultsmentioning
confidence: 99%
“…23) Additionally, it was reported that qdoI encodes a quercetin 2,3-dioxygenase (EC 1.13.11.24) that converts quercetin to 2-protocatechuoyl-phloroglucinol carboxylic acid and carbon monoxide. 24) Further detail characterization revealed that this enzyme is also able to convert other flavonols, such as fisetin, tamarixetin, and galangin, to the corresponding depsides by a similar C-ring cleavage reaction, although its catalytic activity toward fisetin is relatively low. 25) In contrast to qdoI, there is little information about yxaH, except that it is predicted to encode a membrane protein by the sequence information.…”
mentioning
confidence: 99%
“…3). A QdoR mutant capable of responding to The qdoI gene, one of the LmrA/QdoR regulon members, encodes quercetin 2,3-dioxygenase, which forms a dimer (two rotundate rectangles) 24) and catalyzes the C-ring cleavage of flavonols, as illustrated. 29) various flavonoids can be created by substituting the residues in the flavonoid-interacting domain probably including these three aromatic residues, and this mutant would be available as a novel biosensor to detect various flavonoids and related compounds in such a way as to introduce its gene into the B. subtilis strain carrying a reporter-fusion construct similar to that used in this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,9,10) The crystal structures of the enzymes from A. japonicus and B. subtilis revealed that both enzymes belong to the bicupin family, which accommodates metal ions in their catalytic active sites, formed by characteristic -barrel domains. 8,11) While the fungal enzyme contains Cu 2þ , 8,12) the enzyme from B. subtilis is assumed to prefer Mn 2þ as a cofactor, 13) but its recombinant protein has been purified as an iron enzyme from Escherichia coli. 5,11) On the other hand, the Streptomyces sp.…”
mentioning
confidence: 99%